“Mum, when we die, what do you think happens?” A qualitative study of views on death education among Spanish families - Serrano Manzano, Bianca Fiorella; Rodríguez Herrero, Pablo; de la Herrán Gascón, Agustín (Death Studies, 2023)
We developed a study to determine perceptions of death education among parents of Spanish schoolchildren aged 3–18 years. We used a qualitative approach, using focus groups and interviews in six state schools. Notable findings were death-related issues are of interest to families, parents recognized the educational potential of teaching death issues, and they called for training in the Pedagogy of Death for both themselves and teachers. In death education, it is important to take families’ views into account, acknowledging their authority and contributions, to improve schools and education for both children and parents.
Keywords: qualitative study; death; education; Spanish families; Scopus; JCR